Effect of Different Organic Fertilizers Application on Soil Organic Matter Properties. (15th December 2017) - Li, Shuyan; Li, Jijin; Li, Guoxue; Li, Yangyang; Yuan, Jing; Li, Danyang
ABSTRACT: The aim of this study was to investigate the effect of application of different organic fertilizers (general organic fertilizer, GOF; biogas residue, BR; refined organic fertilizer, ROF) as compared to no fertilizer on the composition of the soil organic matter. Different scales of experiment (sand filtration tube, pot, and field plot experiment) were conducted to study the effect of organic fertilizers. The results showed that application of organic fertilizer can significantly increase soil organic matter and improve its quality. The content of soil organic carbon and humus increased with the growing of fertilization within a certain range (0∼38 t ha −1 ). In sand filtration tube experiment, ROF can significantly increase the quality of humic acid (HA)/ fulvic acid (FA), while it had little effect on the quality of HA/FA in the pot and plot experiment. In the field plot experiment, application with mid-dosage (38 t ha −1 ) of ROF can improve total organic carbon (TOC), HA and FA (by 70%, 89%, and 74%, respectively) compared with the control, and it had the best effect of all. BR for its incomplete fermented, had the worst effect of all. Therefore, ROF with 38 t·ha −1 could be used as the optimal fertilization scheme for the purpose of improving soil organic carbon.